2022
DOI: 10.1111/bph.15816
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic and pharmacological studies on protein‐engineered hirudin variants of Hirudinaria manillensis and Hirudo medicinalis

Abstract: Background and Purpose Hirudin variants are the most powerful thrombin inhibitors discovered to date, with a lower risk of bleeding than heparin. For anticoagulation, the C‐termini of hirudin variants bind to the exocite I of thrombin. Anticoagulant effects of gene‐recombinant hirudin are weaker than natural hirudin for the reason of lacking tyrosine O‐sulfation at C‐terminus. Experimental Approach An integrative pharmacological study was carried out using molecular dynamic, molecular biological and in vivo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Thrombin is a central regulator in the coagulation cascade and inflammation process. In the process of venous thrombogenesis, several thrombin inhibitors with pharmacological profiles different from the conventional anticoagulant heparin are currently in clinical use for thromboembolic indications 37 . One of them is the direct thrombin inhibitor recombinant hirudin 37 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thrombin is a central regulator in the coagulation cascade and inflammation process. In the process of venous thrombogenesis, several thrombin inhibitors with pharmacological profiles different from the conventional anticoagulant heparin are currently in clinical use for thromboembolic indications 37 . One of them is the direct thrombin inhibitor recombinant hirudin 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In the process of venous thrombogenesis, several thrombin inhibitors with pharmacological profiles different from the conventional anticoagulant heparin are currently in clinical use for thromboembolic indications 37 . One of them is the direct thrombin inhibitor recombinant hirudin 37 . In the artery, platelet aggregation may play a crucial role in thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An integrative analytical approach was employed in a study published in the British Journal of Pharmacology by Yan Sun and et al 6 to clarify the anticoagulant effects of C-terminusmodified hirudins, HV1 and hirudin variant 2 of Hirudinaria manillensis (HM2). In umbrella sampling of the changes in the Gibbs free energy in the molecular system when the Cterminus of hirudin was pulled away from human thrombin, it was found that the Asp61 mutation of HM2 to Ala decreased the binding free energy of the HM2 C-terminus to thrombin, with the Coulombic potential energy playing a substantial role (unpublished data), whereas the Glu60Asp (E60D) and Ile62Asp (I62D) double mutation enhanced the binding free energy.…”
mentioning
confidence: 99%